Geohazards and environmental degradation in some of the urban areas of Nepal - Kaphle, KP; Rimal, LN; Duvadi, AK; Piya, B; Nepali, D (Journal of Nepal Geological Society, 2008)
Nepal lies in the central part of the seismo-tectonically active Himalayan belt. It is prone to natural hazards like earthquake, flood, landslide, debris flow, glacial lake outburst flood (GLOF), sinkholes, windstorm, thunder etc. Natural hazards bring the disasters in vulnerable areas and disturbs the social system, degraded the environment, aggravate the poverty and eco-system in the affected areas. In the last 23 years natural disasters had caused tremendous losses of lives (about 22,000 people), properties, severe damage of infrastructures costing billions of dollar, and overall set back of development and consequently GDP loss and environment degradation. Their frequency is also increasing due to improper land use, haphazard settlements, unplanned infrastructure development, high population growth rate, uncontrolled multiple human activities etc. Both natural and man-made hazards are deteriorating the natural environments mostly in urban areas. Since there is no effective weather forecasting and early warning system for such disasters the vulnerable people hardly find time to reach safe places and save from possible disaster. Previously the Government of Nepal put its efforts mainly on post disaster activities like rescue, relief and rehabilitation. Only after the Dig Tso glacial lake outburst flood in 1985, earthquake in eastern Nepal in 1988, Flood and Landslide disaster in Central Nepal in 1993 and their severe effects causing tremendous loss of lives, properties and damage of infrastructures, the government and the people realized the importance of predisaster preparedness. For preparedness and mitigation of hazards the geological, engineering and environmental geological, geomorphological and land use maps, hazard maps and hydrological information are extremely important. Now, the government and the people are a bit aware of disaster events and their devastating results. They also realized that the effect of disasters can be reduced considerably if the people are timely well prepared to face such disasters. After having the experiences of the above-mentioned disasters the government has developed the capabilities in emergency response. As a result logistic support management system is fairly improved but more efforts are warranted to identify hazard risk areas and make the people aware of the possible hazards. In this respect Engineering and Environmental Geological Maps of major cities prepared by Department of Mines and Geology could be one of the guides for Planners, Engineers, Decision makers and the people to be familiar with such hazards and prepared accordingly. One of the examples is frequently appearance of sinkholes in different parts of Pokhara city and recently appeared large sinkholes in Chipledhunga/ Newroad near to the office of Pokhara Sub metropolitan City indicate that such maps are valuable guide for infrastructure development planning, disaster management etc. Under the provision given in Natural Calamity Relief Act 1982, Natural Disaster Relief Committees like central, regional, district and village (local level) have been formed. Central Disaster Relief Committee (CDRC) and District Disaster Relief Committee (DDRC) play very active role in close cooperation and coordination with UN bodies, Nepal Red Cross Society, NGOs and INGOs in post disaster activities like response, rescue and relief operations, and rehabilitations works. In 1994 the Yokohama Strategy for a Safe World provided guidance on reducing disaster risk. The Government of Nepal had prepared the National Building Code in 1994 and the first National Action Plan for disaster management in 1996 and partly implemented it. The Action Plan has been updated in 2005 but still sufficient importance is not given for preparedness at any level except enforcement of national building code in some of the municipalities, some announcement on radio and television about the precautionary measures for fire in dry season, epidemic in rainy season, daily weather forecast and early warning system for Tso Rolpa glacier lake and celebrating earthquake day to make the people aware of earthquake. As a part of preparedness the Government organizations, UN agencies, NGOs and INGOs have started to make the people aware of various types of disasters and their possible effects by organizing Workshop/Seminars, giving training, rehearsal, drill etc. They are also lunching disaster management programs in most vulnerable 20 districts. At the same time the concerning Government departments are preparing and publishing hydrological and meteorological information, geological maps, hazard maps, engineering and environmental geological maps which are quite helpful for infrastructure development planning, disaster management, environment protection in urban as well as other parts of the country. Recently to meet the Millennium Development Goals (MDGs) the government is exercising to make development work programs compatible with the disaster management so that to reach the national goal as identified by poverty reduction strategy paper (PRSP) to alleviate the poverty in the country. Reform in the existing Natural Calamity Relief Act 1982 is necessary so as to give more emphasis in disaster preparedness and mitigation. Similarly formulate the policy guidelines, prepare hazard maps of the whole country and engineering and environmental geological maps of all the major cities/town, identify the vulnerable areas categorically in these maps, develop early warning system for major disasters and all these information should be provided (make available) to the peoples working in the infrastructure development, planners, decision makers, all stakeholders and the people at large. All these works will help in preparedness, disaster mitigation, environment protection and over all disaster management in the country. This paper is based on the compilation of the works carried out by the authors in the last few years and other available information. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.23